2008
DOI: 10.1016/j.mce.2007.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Selective agonism in somatostatin receptor signaling and regulation

Abstract: SummaryThe five somatostatin receptor subtypes, named sst1 to sst5, activate both distinct and common signaling pathways and exhibit different patterns of receptor regulation. Until recently it was believed that once a particular somatostatin receptor was activated by an agonist, all the downstream signaling and regulatory effects characteristic of that receptor subtype in that cellular environment would be triggered. Thus, differences in the actions of somatostatin analogs between tissues were attributed to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 42 publications
1
42
0
1
Order By: Relevance
“…Moreover, it has been suggested that different SSA, in the same cell type, may elicit differential effects, due to the activation of different subsets of intracellular mediators. This phenomenon, also named biased agonism, seems to depend on the typical agonist-receptor interactions (Schonbrunn 2008, Ben-Shlomo et al 2009, Cescato et al 2010. In two recent in vitro studies octreotide and pasireotide (SOM 230) have been demonstrated to modulate sst 2A receptor phosphorylation and trafficking in a clearly distinct manner, despite their approximately similar binding affinity to this SSTR subtype (Poll et al 2010).…”
Section: Ss and Da Analogs Treatment In Endocrine Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been suggested that different SSA, in the same cell type, may elicit differential effects, due to the activation of different subsets of intracellular mediators. This phenomenon, also named biased agonism, seems to depend on the typical agonist-receptor interactions (Schonbrunn 2008, Ben-Shlomo et al 2009, Cescato et al 2010. In two recent in vitro studies octreotide and pasireotide (SOM 230) have been demonstrated to modulate sst 2A receptor phosphorylation and trafficking in a clearly distinct manner, despite their approximately similar binding affinity to this SSTR subtype (Poll et al 2010).…”
Section: Ss and Da Analogs Treatment In Endocrine Tumorsmentioning
confidence: 99%
“…The intracellular pathways activated by SSTR activation appear different in different types of tumor cells and depend on the specific SSTR distribution pattern, signaling elements, as well as to receptor desensitization, internalization, and cross talk (Lahlou et al 2004, Schonbrunn 2008. Moreover, it has been suggested that different SSA, in the same cell type, may elicit differential effects, due to the activation of different subsets of intracellular mediators.…”
Section: Ss and Da Analogs Treatment In Endocrine Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main structural and functional features of ssts, including their pharmacology, signalling, endocytosis and recycling, have been extensively characterized using both primary cell cultures and, specially, cell lines stably transfected with different receptors from diverse species, and this information has been carefully reviewed (Moller et al, 2003;Jacobs and Schulz, 2007;Schonbrunn, 2007;Siehler et al, 2007, in …”
Section: Homodimerization Of Somatostatin Receptorsmentioning
confidence: 99%
“…[23,24,26] Nevertheless, the natural ligands of SSTR1-5 can bind all somatostatin receptors with high affinity.…”
Section: Short Synthetic Analogues Of Somatostatinmentioning
confidence: 99%